(3GdKbGaI GdQbejI (B:s (3QDjI eYGUQI (B/s - (3jhSa, ahRj s ((3YeGf (B:s (3OGQ CSGeI ddWHGYI h GdfTQ h GdJhRjY ,s, 2022)
(3Ef GdeTgO GdLOjO GdPj aQVJg GdKhQI GdQbejI Ydi GdeLJeYGJ GdEfSGfjI cGaI Ohf GSJKfGA HJWHjbGJgG GdeJYOOI GdhSGFW h GdefUGJ GdJhGUdjI GdGLJeGYjI GdJj de Jcf eYQhaI ef Pj bHd bO CaQRJ HeG jYQa HGdEYdGe GdLOjO (B.(3EPCUHM dGYHG egeG hQbeG UYHG h JSjO ecGfG QFjSjG aj GdOQGSGJ h GdHMhK GdEYdGejI h GdGLJeGYjI HYO Cf CNP jRGMe Ef de jcf jSGHb GdCSQI h GdeOQSI h GdeLJeY aj EMOGK Ndd Hfjhj hGVM GdeYGde aj eSGb GdJfTFI GdGLJeGYSI h Jchjf GdTNUjI h cCf GdEYdGe GdLOjO CNP ecGf GdUOGQI h HOC jaQV hLhOg GdeJbOe h HTcd eDKQ aj cd GdefXheI GdbjejI h GdCNdGbjI ddfGS (B.s
(3HjHd U(B367-384s
Keywords: (3GdCfJQfJs; (3GdJQHjIs; (3Yde GdELJeGYs; (3ehbY GdJhGUd GdGLJeGYj s